Variability of Shear Wave Velocity using Different Frequencies in Acoustic Radiation Force Impulse (ARFI) Elastography: A Phantom and Normal Liver Study - Chang, S.; Kim, M.-J.; Kim, J.; Lee, M.-J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To assess the variability of shear wave velocity (SWV) from acoustic radiation force impulse (ARFI) elastography at various depths using different frequencies.Materials and Methods: ARFI elastography of the elasticity phantom and normal liver was performed at different depths (2 – 5 cm) with convex (1 – 4 MHz) and linear (4 – 9 MHz) probes. Ten valid SWV measurements at each depth were performed. This was repeated ten times with the phantom and performed in eight healthy volunteers (M:F = 3:5, age 20 – 34 years). The mean value and standard deviation of the SWV were calculated.Results: In both the phantom and liver, the mean velocities as measured by two probes at the same depth were different. Variabilities of SWV at different depths were also different for the two probes. The depth with lower variability in the phantom was 4 and 5 cm with a convex probe and 2 cm with a linear probe. In the liver, the depth with lower variability was 4 cm with a convex probe and 3 and 4 cm with a linear probe. In comparative analysis of the two probes, the linear probe displayed a lower variability at a depth of 2 and 3 cm in the phantom and at 3 cm in the liver, whereas the convex probe displayed a lower variability at a depth of 4 cm in both the phantom and the liver.Conclusion: SWVs and variability are different depending on the depth and the frequency used. SWVs with a low frequency probe had a tendency to be higher at the same depth. To reduce variability of SWV, a high frequency probe is recommended for a depth of 2 – 3 cm, and a low frequency probe is recommended for a depth of 4 – 5 cm.
Keywords: acoustic radiation force impulse-imaging; phantom; liver; variability